2012
DOI: 10.5194/hess-16-2723-2012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical variability at the Upper Paraguay Basin and Pantanal wetland

Abstract: Abstract.Compartmentalization is a prerequisite to understand large wetlands that receive water from several sources. However, it faces the heterogeneity in space and time, resulting from physical, chemical and biological processes that are specific to wetlands. The Pantanal is a vast seasonally flooded continental wetland located in the centre of South America. The chemical composition of the waters that supply the Pantanal (70 rivers) has been studied in order to establish a compartmentalization of the wetla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
(25 reference statements)
0
34
0
3
Order By: Relevance
“…4b) could be attributed either to local soil transformations involving redox processes or to fertilization pollutants from an extensive agricultural area located upstream on the plateau, which consists mainly of a combination of both KCl and (NH 4 ) 2 SO 4 enriching agents. Overall, the waters in the region result from simple concentration and dilution of one original source, the chemical composition of which is close to that of the Taquari River (Rezende-Filho et al 2012). The sum of the contribution to the total variance for both factorial axes 1 and 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4b) could be attributed either to local soil transformations involving redox processes or to fertilization pollutants from an extensive agricultural area located upstream on the plateau, which consists mainly of a combination of both KCl and (NH 4 ) 2 SO 4 enriching agents. Overall, the waters in the region result from simple concentration and dilution of one original source, the chemical composition of which is close to that of the Taquari River (Rezende-Filho et al 2012). The sum of the contribution to the total variance for both factorial axes 1 and 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The second set (TR) consists of 74 sites collected in 2004 along a north-south transect from the Brazilian Agricultural Research Corporation's (EM-BRAPA) experimental farm (Nhumirím farm) to the margins of the Negro River. This second sample set was described in Rezende-Filho et al (2012) and was chosen so as to intersect the regional drainage that is oriented eastnortheast-west-southwest, therefore maximizing the variability. The first two data sets are georeferenced.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rezende Filho et al (2012) analyzed the chemical composition of the main rivers flowing into the Pantanal and observed that the São Lourenço river has alkaline-sodic waters that, when concentrated, favor control of Ca 2+ by formation of carbonates, resulting in pH above 8.0 (Al-Droubi et al, 1980). The geomorphology of the flood plain of the São Lourenço River has several depositional lobes at different stages of dissection.…”
Section: Introductionmentioning
confidence: 99%